3(y+-2)+-1=1

Simple and best practice solution for 3(y+-2)+-1=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(y+-2)+-1=1 equation:


Simplifying
3(y + -2) + -1 = 1

Reorder the terms:
3(-2 + y) + -1 = 1
(-2 * 3 + y * 3) + -1 = 1
(-6 + 3y) + -1 = 1

Reorder the terms:
-6 + -1 + 3y = 1

Combine like terms: -6 + -1 = -7
-7 + 3y = 1

Solving
-7 + 3y = 1

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + 7 + 3y = 1 + 7

Combine like terms: -7 + 7 = 0
0 + 3y = 1 + 7
3y = 1 + 7

Combine like terms: 1 + 7 = 8
3y = 8

Divide each side by '3'.
y = 2.666666667

Simplifying
y = 2.666666667

See similar equations:

| 6(y-1)=3y-15 | | 2*x+x^2+y^2+17=12*y | | 2x^2-10d-9=0 | | -6p=3(2p-3)-4(-10+4p) | | 3y+-6+-1=1 | | 138-1/7y | | 6x^3+28x^2+16x= | | 7(3y-5)+2(4y+3)= | | y^2+17=12*y | | 0.3(n-50)=0.4-0.2(n-7) | | -2x+16y=-14 | | 5-3/2u-7 | | 7x+6(-6+8x)= | | 19-12v/53 | | ((.5)h^2+1)= | | 4x+4x=32 | | 6x^2+6x-13=36-29x | | 14-2/3u8 | | 2x+6x+9= | | 12-9/4v | | 2x^2-24x+70= | | -42v/5 | | -2.2+u/4=-8.6 | | 6x^2+4x-17=39-37x | | x^2+x+1=x^2+ax+b | | 13m=-19+84 | | -x/8-5/2 | | (n-2)*180/n=179 | | 1/(7-j2) | | 1/(7-2j) | | 3.14*8.6*12.7*1/3 | | 6/5-16y |

Equations solver categories